Literatur Review: Consumer Protection in Transactions of Tartar Removal Products on E-Commerce: A Legal and Policy Review - Ida Ayu Dinda Laksmi; I Nyoman Bagiastra; Luh Nyoman Alit Aryani (Indonesian Journal of Global Health Research, 2025)
The rapid growth of e-commerce has significantly transformed consumer purchasing behavior, including in the health and personal care sectors. However, the online sale of tartar removal products raises serious concerns regarding consumer protection, product safety, and regulatory oversight. This study aims to examine the adequacy of the existing legal framework and policy mechanisms in protecting consumers who purchase tartar removal products through e-commerce platforms.Methods: This research employed a literature review design using a comprehensive strategy. Articles were sourced from international research journal databases accessed via the internet, specifically ScienceDirect, PubMed, and Google Scholar. All searches were conducted in March 2025, focusing on articles published between 2016 and 2024. The keywords used in this literature review were adapted from Medical Subject Heading (MeSH) terms, including "consumer protection in e-commerce transactions," "tartar removal products," "e-commerce platforms," and "legal and policy aspects." The initial search yielded 1098 results, of which 711 were duplicates. Of the 387 remaining results, 29 were retained after a title and abstract review. Following a full-text review, 11 articles were included in the study. Charting and theme identification were conducted by a single author (R.C-D).Results:The study identified major challenges, notably the lack of legal protection for consumers. The absence or weakness of legal safeguards in transactions involving tartar removal products has led to several significant issues, including misleading product claims, a lack of mandatory certification, limited enforcement capacity, and inadequate digital infrastructure for transaction monitoring. By analyzing relevant laws, regulations, and case studies, this study highlights the gaps in current consumer protection practices and proposes policy recommendations to strengthen legal protection. These include reinforcing regulatory frameworks, enhancing technology-based monitoring, and promoting consumer education initiatives.Conclusion: The findings emphasize the need for a more adaptive and proactive legal approach to create a safer e-commerce environment, particularly in sectors impacting public health.